Studi Kasus: Identifikasi Dan Penanganan Kesulitan Mahasiswa Dalam Memahami Radiasi Benda Hitam Melalui Simulasi Interaktif Phet Colorado - Br Ritonga, Karyn Arme Septia; Pasaribu, Monika Dian Sari; Br. Sinurat, Yeni Rosanti (Innovative: Journal Of Social Science Research, 2024)
Students' understanding of the concept of black body radiation is often a challenge in learning modern physics. This research aims to identify student difficulties and offer solutions through PhET Colorado's interactive simulation. Using a qualitative approach, three Medan State University students from 2020 and 2021 were used as research subjects. Data obtained from a questionnaire revealed their understanding, difficulties and perceptions of black body radiation. The results show the main difficulties in the form of understanding the radiation spectrum, the relationship between wavelength and energy, and the application of Planck's law. To address this, PhET Colorado simulations were implemented to visualize concepts interactively and through virtual experiments. This simulation is effective in increasing student understanding, based on feedback and observations. This study recommends interactive simulation as an innovative learning method for complex physics material.